Os vestígios materiais de uma herança cultural pastoril nos campos neutrais - Oliveira, Osvaldo André (2010)
The lands of Southern Brazil comprising the municipalities of Santa Vitória do Palmar and Chui, during the process of colonial occupation, were classified as neutral ground. In this territory still hold the remains of a pastoral heritage: the Stables of Palmas. The Stables of Palmas found in the landscape are square and circular structure consisting of palm Butia capitata. Therefore, the general aim of this research is to georeference the Stables of Palmas in order to record the traces of human action that may corroborate or refute the hypothesis that the Stables of Palmas in neutral camps are evidence of a cultural heritage building threatened with extinction. Once they are exposed in areas of agricultural production, cattle ranching, urban growth and weather. Therefore, this production agropastoral destroyed (and continues destroying the trees) deep folds of the palms. However, the interest in researching the Stables of Palmas in neutral camps rests with the need to record these material traces of a pastoral heritage that, being a tree, certainly over time will disappear. However, even time can bring relevant information to regional history, on the historical process of occupation and exploitation of the land called the neutral ground. This dissertation proposes not only to record information, but can also promote further research on this forgotten region in Southern Brazil. Strengthen local identity and memory, providing grants to educational projects to the community in general and finally, the interpretation of landscape transformation that compromises this cultural heritage.